Analyzing the Effectiveness of Revitalization Program. Case: Cihapit Traditional Market - Fatmawati, Fiqi; Lantu, Donald Crestofel (Journal of Business and Management, 2017)
Abstract.The existence of traditional market was shifted because of the number modern market was come up and the internal problem of market such as messy, dirty, and uncontrol. It needs to revitalize the traditional market to face the challenges through the revitalization program. Cihapit market is one of the market in Bandung. It has done the revitalization program. However the problem still came up after the revitalization was held. For that reason, it needs evaluation to know what the achievemen, the result of the program and determine whether the program that has been done. So, the purpose of this study aims to evaluate the program and creates recommendation of revitalization program in the future. A literature review that used are evaluation criteria of public facilities, it consists of effectiveness, efficiency, adequacy, flatness, responsiveness, and accuracy, and benchmarked of revitalization program of best traditional market in Indonesia as the foundation of the researcher to built the recommendation.Â  In this study, researchers applied the action research methodology. It consists of diagnosis, action planning, action taking, evaluation, and reflection. In analyzing the data, researchers used narrative analysis based on the result of documentation, report of program, interviews, and observation. The result is the evaluation of program was not effective and not efficient. The adequacy criteria conclude that it has suitable with the problem and market needs but it still needs an improvement. In flatness criteria result, it did not fulfill the expectation of customer, traders, and market manager. However it has positive responses from all of market user. Also it has raised number of visitor, but it did not change the income of traders. The recommendation of revitalization program in the future are traditional market management which used principal of cooperatives, creates SOP, and improvement service on public facilities in market.Â Keyword :Traditional Market, Revitalization, Evaluation, Public Facilities, Action Research